Evaluating the Implementation of E-government in Public Service Delivery: A Case Study of the Pahandut District Office, Palangka Raya City - Sadar Sadar; M. Riban Ratia (Journal of Government Insight, 2025)
This study aims to evaluate the implementation of e-government in public service delivery at the Pahandut District Office, Palangka Raya City. The analysis focuses on describing the level of implementation based on technological infrastructure readiness, human resource capacity, supporting policies, and community acceptance; identifying enabling and inhibiting factors; and assessing the extent to which e-government contributes to efficiency, effectiveness, and public satisfaction. A qualitative descriptive approach was employed, utilizing in-depth interviews, direct observation, and documentation involving district officials and service users. The findings indicate that the implementation of e-government in Pahandut District has performed reasonably well, supported by adequate technological infrastructure, improved bureaucratic competence, and a generally positive public response toward digital services. Nevertheless, several challenges persist, including unstable internet connectivity, limited supporting facilities, and the incomplete integration of inter-agency systems. Overall, e-government has contributed positively to enhancing the efficiency and transparency of public services. This study underscores the importance of strengthening human resource capacity, maintaining digital infrastructure, and improving inter-agency coordination to ensure more optimal and inclusive e-government implementation at the local level